Progress Report to the International Monetary and Financial Committee on Fund Initiatives to Promote Avian Flu Preparedness. (Policy Papers; Policy Paper, 2006)
There is widespread concern about the possibility of an avian flu pandemic and its implications for humans, and for the global economic and financial system. While the H5N1 virus cannot transmit efficiently from human to human in its present form, a mutation allowing such transmission could lead to a pandemic that might have high costs. Accordingly, the Fund has been active in raising awareness about the potential economic and financial risks of a pandemic, and in helping member countries to undertake contingency planning in their financial sectors.